Supporting Digital Era Through Implementation of Discovery Learning and TPACK Framework to Increase Student’s Learning Outcomes and Interest - Nisa', Varradiah Choirun; Novita, Dian; Wiyati, Arni; Rahinawati, Yuti (Universitas Lampung, 2023)
Supporting Digital Era Through Implementation of Discovery Learning and TPACK Framework to Increase Student’s Learning Outcomes and Interest.This study aims to increase student’s interest and learning outcome by implementing discovery learning and the TPACK framework in chemical bonding material. This study is a collaborative class action research with quantitative and qualitative methods. The subjects of this study were 33 students of XI-3 from Senior High School 6 Surabaya. The instruments used in this study were pre-research questionnaire sheets, teaching modules using the discovery learning model and TPACK framework, interest questionnaires, student activity observation sheets, and posttest sheets per cycle. The research was conducted in three cycles. The data analyzed descriptively and obtained were learning using discovery learning and TPACK among cycles 1, 2 dan 3 experienced an increase in student’s learning outcomes and interest supported with the increasing of activity in observed stimulus, involved in problem statements, accessed materials and technology, analyzed and processed data, and presented the result. The average of learning outcomes in cycle 1 was 77 and went up to 90 and 97 in cycles 2 and 3 while the classical mastery from all cycles went up from 67% to 91% and 100%. Student’s interest in learning chemistry also went up through each cycle seeing through the percentage of the number of students in the high interest category from 21% in cycle 1 to 58% in cycle 2 and 87% in cycle 3. From these data on student’s learning outcomes and interest, it can be concluded that the implementation of discovery learning and the TPACK framework was effective to increase the student’s learning outcomes and interest in chemistry class.DOI: 10.23960/jppk.v12.i3.2023.02